Financial Literacy: Its Paradoxical Effect on MSME Financial Management in the Digital Era - Dhea Resthy Ananda; Muhammad Ilham Pakawaru; Sugianto Sugianto; Rika Febby Rhamadhani (Advances in Taxation Research, 2026)
Purpose: This study investigates the effects of financial literacy and financial technology (e-wallet usage) on the financial management practices of micro, small, and medium enterprises (MSMEs) in Palu City. Research Method: A quantitative research design was employed using primary data collected through questionnaires administered to MSME owners. The proposed relationships were examined using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS. Results and Discussion: The results indicate that financial literacy significantly influences MSME financial management. However, higher levels of financial knowledge do not automatically translate into more effective financial management practices. In contrast, e-wallet usage exhibits a positive but statistically insignificant effect, suggesting that digital payment adoption alone is insufficient to improve financial management. These findings reveal a persistent gap between financial capability, technology adoption, and the practical implementation of sound financial management. Implications: Policymakers should complement financial literacy and digitalization initiatives with practical training that strengthens MSMEs' ability to integrate financial knowledge and digital technologies into everyday financial decision-making. Originality: This study extends the MSME finance literature by simultaneously examining financial literacy and e-wallet adoption within an emerging economy context, demonstrating that digital financial technology does not necessarily enhance financial management unless supported by adequate financial capability and effective managerial application.